(untitled) (Journal of Interdisciplinary Insights, 2026)
Against the backdrop of structural transformation and intensified competition in China’s private higher education sector, student management has emerged as a critical determinant of institutional quality and sustainability. This study examines the current conditions, challenges, and improvement pathways of student management in private undergraduate institutions in Inner Mongolia, China, using Inner Mongolia Honder College of Arts and Sciences as a case study. Drawing on policy analysis, institutional documents, and comparative practices across private universities, the study systematically analyzes key problem areas, including academic culture development, daily behavioral governance, mental health education, employment guidance, counselor workforce capacity, institutional mechanisms, and regional and cultural adaptation. The findings reveal that student management in private undergraduate institutions is constrained by fragmented governance structures, insufficient professionalization of management teams, limited resource investment, and inadequate integration of digital and developmental approaches. In response, this study proposes a phased reform framework encompassing people-centered institutional design, professional workforce development, digital transformation of student services, culturally inclusive management practices, and regionally distinctive development strategies. By shifting student management from a control-oriented paradigm toward a developmental and quality-oriented model, this research offers actionable policy implications and a replicable governance framework for private undergraduate institutions, particularly those in ethnically diverse and less-developed regions of China.